2007
DOI: 10.1074/jbc.m704481200
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat Activates Dual Nox Pathways Leading to Independent Activation of ERK and JNK MAP Kinases

Abstract: Human immunodeficiency virus, type 1 Tat is known to exert pleiotropic effects on the vascular endothelium through mitogen-activated protein (MAP) kinases, although the signaling pathways leading to MAP kinase activation are incompletely understood. We focused on proximal pathways potentially governing downstream MAP kinase activity by Tat. Within 2 min, Tat activated both Ras and Rho GTPases in endothelial cells, leading to ERK phosphorylation by 10 min. Notably, Rac1 was necessary for downstream activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 34 publications
2
50
0
Order By: Relevance
“…To gain further support for the role of Nox4 in specific ER signaling events, we examined the involvement of other known signaling pathways, focusing on the agonist Tat. When stimulated acutely with Tat, RhoA and Ras are transiently activated (44). Under these conditions, RhoA acts upstream of Nox4, which in turn leads to downstream Ras activation.…”
Section: Resultsmentioning
confidence: 99%
“…To gain further support for the role of Nox4 in specific ER signaling events, we examined the involvement of other known signaling pathways, focusing on the agonist Tat. When stimulated acutely with Tat, RhoA and Ras are transiently activated (44). Under these conditions, RhoA acts upstream of Nox4, which in turn leads to downstream Ras activation.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19][20]. These differences in regulation, activation mechanism, subcellular location, and ROS generation translate into isoform-specific actions in isolated cellular models (9,19,22,33). In the heart, previous studies in mouse models of defective Nox2 activation or its deletion showed that Nox2 is detrimental during remodeling, causing increased hypertrophy, apoptosis, and contractile dysfunction (10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Although Nox4 is a constitutively active ROS-generating enzyme, increased expression of mRNA, protein, and ROS has been detected in response to inflammatory stimuli. Recent work suggests that Nox4-derived ROS are involved in transforming growth factor ␤ (TGF-␤)-induced fibrosis, ER stress, human immunodeficiency virus type 1-activated cell signaling, beta interferon-regulated transcription, and Toll-like receptor 4-mediated pathways (10,14,(51)(52)(53)72). However, little is known about the function of Nox4 in the liver under inflammatory conditions.…”
mentioning
confidence: 99%